The Austrian policy towards elementary bilingual education in Southern Carinthia and its changes between 1958 and 1988 - Klemenčič, Matjaž (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2011)
The article deals with the Austrian policy towards bilingual elementary education. After World War II Austria introduced compulsory elementary bilingual education within almost whole territory of Slovene indigenous settlement in southern Carinthia. Soon after the State Treaty for the Re-establishment of an Independent and Democratic Austria of 1955 was signed the German nationalists sharpened their demands that parents should decide on the language of education of their children. As a result of this pressure the compulsory bilingual elementary education was abolished in 1958. Author deals with the debates in Austrian parliament which led to the passage of new minority school law in 1959, which worsened the positions of Slovene minority.The second part of the article deals with debates and procedures when this law was changed again in 1980s. The changes did not achieve the aims of those who proposed them. The political circumstances after the fall of Berlin Wall and increased importance of Slovene language as one of the official languages of EU again increased the interest in Carinthia for bilingual education.
Keywords: Carinthian Slovenes; koroški Slovenci; manjšine; narodne manjšine; pravno varstvo; manjšinska zakonodaja; zaščita manjšin; school; šolstvo; bilingualism; dvojezičnost; dvojezično izobraževanje; Austria; Avstrija